2013
DOI: 10.1103/physrevc.88.044331
|View full text |Cite
|
Sign up to set email alerts
|

Low-lying dipole strength of the open-shell nucleus94Mo

Abstract: The low-lying dipole strength of the open-shell nucleus 94 Mo was studied via the nuclear resonance fluorescence technique up to 8.7 MeV excitation energy at the bremsstrahlung facility at the Superconducting Darmstadt Electron Linear Accelerator (S-DALINAC), and with Compton backscattered photons at the High Intensity γ-ray Source (HIγ S) facility. In total, 83 excited states were identified. Exploiting polarized quasi-monoenergetic photons at HIγ S, parity quantum numbers were assigned to 41 states excited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
(121 reference statements)
3
28
0
Order By: Relevance
“…3 Interestingly, the previous literature [20,22,23] reported that b 0 as a function of excitation energy was difficult to be described within the statistical model. A maximum of b 0 in the energy domain of the PDR has, e.g., been reported for 94 Mo [23] and for 130 Te [22], whereas b 0 calculated within the statistical model steadily decreases as a function of increasing energy.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…3 Interestingly, the previous literature [20,22,23] reported that b 0 as a function of excitation energy was difficult to be described within the statistical model. A maximum of b 0 in the energy domain of the PDR has, e.g., been reported for 94 Mo [23] and for 130 Te [22], whereas b 0 calculated within the statistical model steadily decreases as a function of increasing energy.…”
Section: Resultsmentioning
confidence: 96%
“…3 Interestingly, the previous literature [20,22,23] reported that b 0 as a function of excitation energy was difficult to be described within the statistical model. A maximum of b 0 in the energy domain of the PDR has, e.g., been reported for 94 Mo [23] and for 130 Te [22], whereas b 0 calculated within the statistical model steadily decreases as a function of increasing energy. This deviation may occur because the statistical model can either not describe the decay behavior of the strongly excited states that are concentrated in the excitation-energy domain of the PDR where also the maximum of b 0 is observed or because the statistical model cannot describe the concentration of strongly excited states in this excitation-energy range.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the method of relative self absorption (RSA) [8,9] allows for the model-independent, direct determination of the ground-state transition width, the total level width, and, consequently, also of the branching ratio to the ground state of individual excited states. On one hand, this technique is well suited to study the decay pattern of lowlying dipole excited states such as those attributed to the PDR, which recently draw a lot of attention [10,11,12]. On the other hand, it provides the opportunity to improve the accuracy of, e.g., calibration standards that are used in NRF measurements [13].…”
Section: Introductionmentioning
confidence: 99%